State and Prospects of Development of Welfare Economics in Ukraine - Койчева, Ольга Семенівна; Койчева, О. С.; Койчева, Ольга Семеновна; Koicheva, Olha S.; Білокур, Євгенія Ігорівна; Білокур, Є. І.; Билокур, Евгения Игоревна; Bilokur, Yevheniia I.; Негара, Родіон Віталійович; Негара, Р. В.; Негара, Родион Витальевич; Nehara, Rodion V. (Dorma Journals Publisher, 2019)
The desire to become an integral part of the European community demands from Ukraine to comply with certain requirements and to conform to the established standards. One of the criteria for compliance is the developed economy, which ensures the interests of the state as a whole and of each member of society separately. For many years our state has been trying to take its "place in the sun" where all its citizens will do well, and everyone will be able to meet his or her needs, despite the fact that they all are different. Ukraine, like almost all post-Soviet states, refers to developing countries, and this factor must necessarily be taken into account when building the modern economy of the country. The economic welfare of a person is determined by many socio-economic factors, such as: level and quality of life, the provision of necessary vital goods, the amount of wages agreed with the necessary and desirable needs. The most important indicator of economic prosperity is the level and quality of life. It is the quality of life that determines the level of provision, the abundance not only of individual citizens, but also of the country, of the nation as a whole. The definition of "welfare" should be traditionally understood as the correspondence between the volume of goods and the volume of needs, the level of implementation of which depends on the level of their manifestation, which is formed under the influence of both internal and external factors, and the financial support necessary for their satisfaction. Factors influencing the presence or absence of welfare and determining its level can be divided into: subjective –psychological features, upbringing, education, environment, outlook, mentality, and objective –the urgent problems of time, the dominant ideology, the type of economic system, economic expectations and the impact of scientific and technological progress. The urgency of the study of the feasibility of the welfare economics is stipulated by the urgent need to improve living standards through the implementation of the specified model of economics in Ukrainian society, which is currently in a deep protracted crisis, constantly faced with the difficulties of the transition period, the emigration of the ablebodied population and other factors that negatively affect the level of life of the population.

Бажання стати невід’ємною частиною європейського співтовариства вимагає від України дотримання певних вимог і відповідати встановленим стандартам. Одним із критеріїв відповідності є розвинена економіка, що забезпечує інтереси держави в цілому і кожного члена суспільства окремо. Наша держава багато років намагається зайняти своє «місце під сонцем», де всі її громадяни будуть добре почуватися, і кожен зможе задовольнити свої потреби, незважаючи на те, що всі вони різні. Україна, як і майже всі пострадянські держави, відноситься до країн, що розвиваються, і цей фактор необхідно обов’язково враховувати при побудові сучасної економіки країни. Економічний добробут людини визначається багатьма соціально-економічними факторами, такими як: рівень і якість життя, забезпеченість життєво необхідними благами, розмір заробітної плати, узгоджений з необхідними і бажаними потребами. Найважливішим показником економічного процвітання є рівень і якість життя. Саме якість життя визначає рівень забезпеченості, достаток не лише окремих громадян, а й країни, нації в цілому. Під визначенням «благополуччя» традиційно слід розуміти відповідність між обсягом товарів і обсягом потреб, рівень реалізації яких залежить від рівня їх прояву, що формується під впливом як внутрішніх, так і зовнішніх факторів, та фінансову підтримку, необхідну для їх задоволення. Фактори, що впливають на наявність чи відсутність добробуту та визначають його рівень, можна розділити на: суб’єктивно – психологічні особливості, виховання, освіта, середовище, світогляд, менталітет, та об’єктивні – актуальні проблеми часу, панівна ідеологія, тип економічної системи, економічні очікування та вплив науково-технічного прогресу. Актуальність дослідження доцільності економіки добробуту зумовлена ​​гострою потребою підвищення рівня життя населення шляхом впровадження зазначеної моделі економіки в українське суспільство, яке наразі перебуває в глибокій затяжній кризі, постійно стикається з труднощами розвитку економіки, перехідним періодом, еміграцією працездатного населення та іншими факторами, що негативно впливають на рівень життя населення.
Koicheva O. State and Prospects of Development of Welfare Economics in Ukraine / O. Koicheva, Ye. Bilokur, R. Nehara // Journal of Environmental Treatment Techniques. - Vol. 7. - Issue 3. - Dorma Journals Publisher, 2019. - P. 377-382.
Keywords: Economics Of Welfare; Happiness; Living Standards Of Population; Economic Needs; Human Factor; економіка добробуту; щастя; рівень життя населення; економічні потреби; людський фактор; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Economics